Three new species of the Harnischia complex from the Sino-Indian Region,with a review of Demicryptochironomus Lenz (Diptera: Chironomidae) - Yan, Chuncai; Sæther, Ole A.; Jin, Zhaohui; Wang, Xinhua (Zootaxa, 2008)
Three new species, Demicryptochironomus (Irmakia) retusus, Microchironomus brochus, and Parachironomus lobus are described and figured as males. Demicryptochironomus (Demicryptochironomus) asamaprimus Sasa et Hirabayashi, D. (D.) chuzequartus Sasa, D. (D.) ginzancedeus Sasa et Suzuki, D. (D.) uresicarinus Sasa, and Demicryptochironomus clarilatus (Guha et Chaudhuri) are re-examined based on type material. Cryptotendipes inawabeceus Sasa, Kitami et Suzuki, C. tamacutus Sasa and Parachironomus harunasecundus Sasa are transferred to Demicryptochironomus as new combinations. Parachironomus inageheus Sasa, Kitami et Suzuki is placed as a junior synonym of Demicryptochironomus ginzancedeus Sasa et Suzuki. The relationships of some genera within the Harnischia complex are discussed. A key to the males of Demicryptochironomus is presented.